Puerarin affects adipose lipolysis and ameliorates obesity by gut microbiota - Li, Zhaoyi; Ye, Yingyan; Lai, Shanglei; Bao, Jianfeng; Fu, Ai (Frontiers in Microbiology, 2025)
BackgroundObesity has become a widespread metabolic disorder, marked by its escalating global prevalence. Puerarin, extracted from Pueraria lobata, one of the traditional homologies of medicine and food, demonstrates anti-obesity properties. Nonetheless, the mechanisms through which puerarin exerts its anti-obesity effects remain to be elucidated. This study seeks to highlight the potential application of puerarin in obesity management and to investigate the underlying mechanisms involving gut microbiota and lipid metabolism.MethodDifferent doses of puerarin were administered to the high-fat diet mice model, and the structure and composition of gut microbiota were analyzed using 16S rRNA sequencing. Q-PCR evaluated the expression of genes related to lipid metabolism.ResultOur findings demonstrate that puerarin treatment significantly reduces body weight and epithelial and beige fat mass. Furthermore, puerarin alters the structure and composition of gut microbiota, which is associated with metabolism. Additionally, puerarin treatment significantly upregulates gene expression, fatty acid transport protein 5 (FATP5) hormone-sensitive lipase (HSL), adipose triglyceride lipase (ATGL) in epithelial and beige adipose.ConclusionPuerarin demonstrates potential in ameliorating obesity by changing the structure and composition of gut microbiota, which enhances the transport of fatty acid and triglycerides hydrolysis within adipose tissue. This study provides a novel perspective on puerarin as a dietary supplement for obesity.